1400 W, a selective inducible nitric oxide synthase inhibitor, mitigates early neuroinflammation and nitrooxidative stress in diisopropylfluorophosphate-induced short-term neurotoxicity rat model - Massey, Nyzil; Vasanthi, Suraj Sundara; Samidurai, Manikandan; Gage, Meghan; Rao, Nikhil; Meyer, Christina; Thippeswamy, Thimmasettappa (Frontiers in Molecular Neuroscience, 2023)
Organophosphate nerve agent (OPNA) exposure induces acute and long-term neurological deficits. OPNA exposure at sub-lethal concentrations induces irreversible inhibition of acetylcholinesterase and cholinergic toxidrome and develops status epilepticus (SE). Persistent seizures have been associated with increased production of ROS/RNS, neuroinflammation, and neurodegeneration. 1400W is a novel small molecule, which irreversibly inhibits inducible nitric oxide synthase (iNOS) and has been shown to effectively reduce ROS/RNS generation. In this study, we investigated the effects of 1400W treatment for a week or two weeks at 10 mg/kg or 15 mg/kg per day in the rat DFP model. 1400W significantly reduced the number of microglia, astroglia, and NeuN+FJB positive cells compared to the vehicle in different regions of the brain. 1400W also significantly reduced nitrooxidative stress markers and proinflammatory cytokines in the serum. However, neither of the two concentrations of 1400W for two weeks of treatment had any significant effect on epileptiform spike rate and spontaneous seizures during the treatment period in mixed sex cohorts, males, or females. No significant sex differences were found in response to DFP exposure or 1400W treatment. In conclusion, 1400W treatment at 15 mg/kg per day for two weeks was more effective in significantly reducing DFP-induced nitrooxidative stress, neuroinflammatory and neurodegenerative changes.